2021
DOI: 10.1002/mrd.23465
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of buffalo granulosa cells in three dimensional culture systems

Abstract: Hanging drop (HD) three-dimensional (3D) culture model for buffalo granulosa cells (GC) was reported to mimic the preovulatory stage of ovarian follicles in our previous study.To further verify its reliability, the present study attempted a comparative transcriptome profile of buffalo GC freshly isolated from ovarian follicles (<8 mm diameter) (FC) and their cultures in normal culture dish (ND or 2D), polyHEMA coated dish (PH) and HD culture systems (3D). Out of 223 significantly (−log2 fold change: >3; p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Despite bioprinting spheroids having been used to study various cancer types such as glioblastoma [53,77], breast cancer [78], pancreatic duct adenocarcinoma [55], osteosarcoma [79] and ovarian cancer [80], there is a lack of studies that validate this model for OSCC. The spheroid bioprinting method might represent an advantageous approach compared to hanging drop cultures [81], organ-on-a-chip [82], and organoids [83] for allowing higher reproducibility, technical simplicity, and the ability to construct heterotypic spheroids with well-nutrient distribution and tumor zone formation [84][85][86]. This approach cooperates in dealing with the lack of appropriate methods to study CIC structures [11,18,87].…”
Section: Discussionmentioning
confidence: 99%
“…Despite bioprinting spheroids having been used to study various cancer types such as glioblastoma [53,77], breast cancer [78], pancreatic duct adenocarcinoma [55], osteosarcoma [79] and ovarian cancer [80], there is a lack of studies that validate this model for OSCC. The spheroid bioprinting method might represent an advantageous approach compared to hanging drop cultures [81], organ-on-a-chip [82], and organoids [83] for allowing higher reproducibility, technical simplicity, and the ability to construct heterotypic spheroids with well-nutrient distribution and tumor zone formation [84][85][86]. This approach cooperates in dealing with the lack of appropriate methods to study CIC structures [11,18,87].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the GCs were cultured with a density of 20,000 cells/10 μl in a six-well culture plate. The 3 μl of media regularly added to each HD nutritional losses replenish losses due to evaporation and cell's metabolism (after every 48 h) [72].…”
Section: D Hanging Drop System Of Buffalo Gcsmentioning
confidence: 99%
“…Although many studies have stressed the importance and superiority of 3D culture, there are few studies on its effects on OGCs. Buffalo OGCs cultured using the hanging drop method mimic the intrafollicular environment (Yadav et al, 2018), and this system was found to be better than the other methods for simulating the inflammatory milieu required for ovulation (Pandey et al, 2021); however, no such studies have been performed on rat OGCs (rOGCs). In our study, we investigated the effects of 2D and 3D cultures of rOGCs on their proliferation using RNA‐seq to analyze the transcriptome differences between two groups, to investigate the effects of 3D culture on the transcript levels of OGCs, and to provide a theoretical basis for attaining the best OGCs for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have stressed the importance and superiority of 3D culture, there are few studies on its effects on OGCs. Buffalo OGCs cultured using the hanging drop method mimic the intrafollicular environment (Yadav et al, 2018), and this system was found to be better than the other methods for simulating the inflammatory milieu required for ovulation (Pandey et al, 2021); however, no such studies have been performed on rat OGCs (rOGCs).…”
mentioning
confidence: 99%